HIV Care Continuum after Rapid Start with Patient Navigation in a Large Urban HIV Clinic in Dallas, TX. - Chow, Jeremy Y.; Gao, Ang; Ahn, Chul; Perez, Gilbert; Nijhawan, Ank E. (AIDS Patient Care & STDs, 2026)
Rapid start of antiretroviral therapy (ART) has been recommended by multiple international and US-based groups because of its ability to decrease time to initiation of ART, virologic suppression, and improve retention in care. However, there has been heterogeneity in the components of rapid start programs. This prospective study examines HIV care continuum outcomes after patient navigation (PN) was added to our large rapid start program in Dallas, TX. Newly diagnosed patients were enrolled in rapid start + PN (n = 199) for 12 months, and HIV care continuum outcomes were compared with historical pre-rapid start (N = 295) and rapid start (N = 244) cohorts. Cumulative incidence curves were used to summarize time to virologic suppression, incorporating death as a competing risk, and stepwise competing-risk regression and logistic regression models were used to build multivariate models to evaluate the associations between rapid start, PN, and time to virologic suppression, and between retention in care and sustained virologic suppression, respectively. Rapid start + PN was associated with increased odds of being retained in care [adjusted odds ratio (aOR) 2.00; 95% confidence interval (CI) 1.32, 3.02; p < 0.01] compared with pre-rapid start. The time to virologic suppression was not significantly different between the three cohorts [pre-rapid (2.50 months), rapid start (2.56 months), and rapid start + PN (2.78 months), p = 0.41], while the odds of sustained virologic suppression in the rapid start + PN group was significantly lower (aOR 0.65, 95% CI 0.44, 0.97; p = 0.04). Though PN had mixed HIV care continuum outcomes, it can be adapted to augment rapid start programs and improve retention in care.